A comparison of book text and Child Directed Speech. Issue 3 (June 2013) - Cameron-Faulkner, Thea; Noble, Claire
This article evaluates the extent to which pre-schoolers' picture books can be viewed as a form of enriched linguistic input. Twenty best-selling picture books were analysed in terms of syntactic constructions and compared with a sample of Child Directed Speech. The findings of the study demonstrate the prevalence of canonical utterances (i.e. those displaying Subject-Verb (Object) ordering) and Complex constructions within the book sample, both types of which occur with very low frequency in everyday Child Directed Speech. It is concluded that the linguistic content of young children's books has the potential to play an important role in children's grammatical development.